The big book for toddlers - Wong, Alice; Tabori, Lena (Welcome Books, 2009)
A special book, celebrating the wonder of youth, filled with classic material guaranteed to occupy, fascinate, and delight toddlers. Designed with vintage illustrations, included are fairytales, activities, songs, games, and nursery rhymes--Publisher description.